Callous-Unemotional Traits in Incarcerated Adolescents - Kimonis, Eva R. (Psychol Assess, 2013)
The presence of callous-unemotional (CU) traits designates a subgroup of antisocial youth at risk for severe, aggressive, and stable conduct problems. As a result, these traits should be considered as part of the criteria for conduct disorder. The present study tests two possible symptom sets (four and nine item criteria sets) of CU traits that could be used in diagnostic classification, assessed using self-report with a sample of 643 incarcerated adolescent (M age = 16.50, SD = 1.63 years) boys (n = 493) and girls (n = 150). Item response theory analysis was employed to examine the unique characteristics of each criterion comprising the two sets to determine their clinical utility. Results indicated that most items comprising the measure of CU traits demonstrated adequate psychometric properties. Whereas the nine item criteria set provided more information and was internally consistent, the briefer four item set was equally effective at identifying youth at-risk for poor outcomes associated with the broader CU construct. Supporting the clinical utility of the criteria sets, incarcerated boys and girls who endorsed high levels of symptoms across criteria sets were particularly at-risk for proactive aggression and violent delinquency.